2021
DOI: 10.3389/fped.2021.674317
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Hyper IgE, but Not the Usual Suspects–Kimura Disease in an Adolescent Female

Abstract: Elevated immunoglobulin E (IgE) levels can be associated with infectious, allergic and inflammatory disorders, and rarely as a manifestation of an inborn error of immunity. Here we report the case of an adolescent female who presented with a gradually enlarging neck mass, lymphadenopathy, eosinophilia and highly elevated IgE levels. Laboratory and histopathologic evaluation revealed an unlikely diagnosis of Kimura Disease. We discuss the differential diagnosis of a neck mass with prominent eosinophils on histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…ALHE exhibits a distinct demographic predilection, typically affecting middle-aged females in all racial groups. Clinically, ALHE patients are less likely to present with adenopathy, and serum IgE levels are often normal, in contrast to KD [ 5 , 14 ]. Other differentials for bilateral parotid/infraauricular masses, as seen in our case, would include lymphoma, salivary gland tumours, and Sjogren's syndrome [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALHE exhibits a distinct demographic predilection, typically affecting middle-aged females in all racial groups. Clinically, ALHE patients are less likely to present with adenopathy, and serum IgE levels are often normal, in contrast to KD [ 5 , 14 ]. Other differentials for bilateral parotid/infraauricular masses, as seen in our case, would include lymphoma, salivary gland tumours, and Sjogren's syndrome [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, angiolymphoid hyperplasia with eosinophilia (ALHE), which may overlap with KD, was also suggested as a differential diagnosis. ALHE was ruled out because salivary gland involvement, peripheral blood eosinophilia, and elevated IgE levels are rare in ALHE, and IgE-positive germinal centers are not seen in ALHE [12] , [13] , [14] . Peripheral blood eosinophilia and high levels of IgE are typical features of KD; however, these findings are also observed in IgG4-RD [12] .…”
Section: Discussionmentioning
confidence: 99%
“…ALHE was ruled out because salivary gland involvement, peripheral blood eosinophilia, and elevated IgE levels are rare in ALHE, and IgE-positive germinal centers are not seen in ALHE [12] , [13] , [14] . Peripheral blood eosinophilia and high levels of IgE are typical features of KD; however, these findings are also observed in IgG4-RD [12] . Clinicopathological overlap between IgG4-RD and KD has been reported [9] ; this was evident in the present case because our patient showed elevated levels of serum IgG4, the presence of >10 IgG4-positive cells/high power field, and a >40% IgG4/IgG ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that in KD, the levels of IL-4, IL-5, IL-10, and IL-13 are high. 17,18 Therefore,…”
Section: Discussionmentioning
confidence: 99%
“…Dupilumab can specifically bind to the type I receptor (IL-4Rα/γc) as well as the type II receptor (IL-4Rα/IL-13Rα) subunit shared by the IL-4 and IL-13 receptor complexes. Previous studies have indicated that in KD, the levels of IL-4, IL-5, IL-10, and IL-13 are high 17,18 . Therefore, a Th2 pathway-targeted agent such as dupilumab (approved by the Food and Drug Administration in March 2019) may be more effective in treating KD.…”
Section: Discussionmentioning
confidence: 99%